Analyzing Attitude Change towards Nuclear Energy after the Fukushima Accident - An Application of Multilevel Modeling - - 배상석; 김동근; 김서용 (Crisisonomy, 2018)
The Fukushima nuclear accident had a significant impact on the attitude change toward nuclear energy. This attitude change critically influences the energy transition, in particular, phaseout of nuclear energy. The purpose of this study is to analyze the determinants of attitude change toward nuclear energy after the Fukushima accident. Since the attitude change is influenced not only by the individual variables but also by the contextual variables, it is necessary to set both the macro country-level variables and the micro individual-level variables as the causal variables of the attitude change. Empirical findings summarize that male, education, religion, risk perception, and trust at the individual level, and operation of nuclear power plant, GDP per capita at the country level had a crucial impact on attitude change from supporting to opposing.
Keywords: Fukushima accident; attitude change; individual-level; country level; multilevel modeling; 후쿠시마 원전사고; 태도변화; 개인수준/국가수준; 다수준 모델링